Does corruption promote emigration? - Friedrich Schneider (IZA World of Labor, 2015)
Knowing whether corruption leads to higher emigration rates—and among which groups—is important because most labor emigration is from developing to developed countries. If corruption leads highly-skilled and highly-educated workers to leave developing countries, it can result in a shortage of skilled labor and slower economic growth. In turn, this leads to higher unemployment, lowering the returns to human capital and encouraging further emigration. Corruption also shifts public spending from health and education to sectors with less transparency in spending, disadvantaging lower-skilled workers and encouraging them to emigrate.
Keywords: D78; H2; H11; H26; O5; O17; 330; corruption; emigration; educational attainment; inequality